Tin-carbon negative electrode material coated with mixed conductive polymer, preparation method of tin-carbon negative electrode material, negative electrode plate, sodium-ion battery and power-related equipment

By using a hybrid conductive polymer to coat the tin carbon negative electrode material in sodium ion batteries, the structural damage problem caused by volume expansion during charging and discharging of pure Sn electrodes is solved, and better interface stability and cycling performance are achieved.

CN119764410AActive Publication Date: 2025-04-04SHENZHEN BTR NEW ENERGY TECH RES INST CO LTD

Patent Information

Application Number
CN202411973955.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

During the charging and discharging process, the existing pure Sn electrodes have structural damage due to volume expansion, making it difficult to form a stable SEI film on the surface, resulting in fast attenuation of battery capacity and poor circulation performance.

Method used

A hybrid conductive polymer is used to coat the tin carbon anode material, including a single tin core, an amorphous carbon shell and a hybrid conductive polymer cladding layer, which has ionic conductivity and electronic conductivity. A stable cladding layer is formed to limit the volume expansion of tin by combining polymer solid electrolyte and electronic conductive material.

Benefits of technology

It effectively suppresses the volume expansion of tin, improves interface stability, and improves the circulation performance and capacity retention rate of sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764410A_ABST
    Figure CN119764410A_ABST
Patent Text Reader

Abstract

The invention provides a mixed conductive polymer coated tin-carbon negative electrode material and a preparation method thereof, a negative electrode plate, a sodium-ion battery and power-related equipment, and relates to the technical field of new energy. According to the preparation method of the mixed conductive polymer coated tin-carbon negative electrode material, a carboxyl-rich organic tin source and a hydroxyl-rich carbon source are taken as raw materials for hydrothermal reaction, the carboxyl-rich organic tin source is firstly heated and decomposed into tin oxide and carboxyl functional groups, and the carboxyl functional groups and the hydroxyl-rich carbon source are subjected to esterification crosslinking; the preparation method comprises the following steps: forming a spherical carbon precursor and a tin oxide precursor, reducing the tin oxide precursor by carbon at a high temperature to generate an elemental tin core in situ, esterifying a cross-linked structure to form an amorphous carbon shell on the surface to obtain a spherical tin-carbon negative electrode material, mixing the spherical tin-carbon negative electrode material with a polymer solid electrolyte and an electronic conductive material, drying, and carrying out microwave treatment to obtain the lithium ion battery negative electrode material. The electronic conductive material receives microwave magnetic field heating, so that the effect of the mixed conductive polymer material and the amorphous carbon shell is enhanced, and a uniform and firm mixed conductive polymer coating layer is formed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of new energy technology, and in particular to a mixed conductive polymer-coated tin-carbon negative electrode material and a preparation method thereof, a negative electrode sheet, a sodium ion battery and electrical equipment. Background Art

[0002] The negative electrode materials of sodium ion batteries mainly include carbonaceous materials, metals (such as Sn, Sb, Ge) and metal oxides. Among them, metal Sn materials have attracted much attention. Metal Sn can form alloys with Na 15 Sn4 has a theoretical capacity of up to 837mAh / g. However, the huge volume expansion effect of pure Sn electrode leads to structural damage, and huge volume expansion occurs during the sodium insertion process. As a result, during the charge and discharge process, the negative electrode active material is easily broken and powdered, and it is difficult to form a stable SEI film on the surface, which leads to the battery capacity decaying too fast and poor cycle performance. Summary of the invention

[0003] The purpose of the present application is to provide a mixed conductive polymer coated tin-carbon negative electrode material and its preparation method, negative electrode sheet, sodium ion battery and electrical equipment, aiming to solve the problem that the capacity of existing pure Sn electrodes decays too fast and the cycle performance is very poor.

[0004] To achieve the above objectives, the present application provides a hybrid conductive polymer-coated tin-carbon negative electrode material, comprising: a single tin core, an amorphous carbon shell coating the single tin core, and a hybrid conductive polymer coating layer coating the amorphous carbon shell, wherein the hybrid conductive polymer coating layer has ionic conductivity and electronic conductivity.

[0005] In some embodiments, the hybrid conductive polymer coating layer includes a polymer solid electrolyte and an electronically conductive material;

[0006] Optionally, the electronic conductive material includes one or a combination of conductive carbon black, conductive graphite, single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, and carbon fibers;

[0007] Optionally, the polymer solid electrolyte includes one or a combination of polyethylene oxide, polyacrylonitrile, and poly(methyl methacrylate);

[0008] Optionally, the mass ratio of the polymer solid electrolyte to the electronic conductive material is 1:100 to 100:1.

[0009] In some embodiments, at least one of the following conditions is met:

[0010] A. The diameter of the elemental tin core is 100-2000nm;

[0011] B. The thickness of the amorphous carbon shell is 10-200 nm;

[0012] C. The thickness of the mixed conductive polymer coating layer is 10-200 nm;

[0013] D. The particle size of the mixed conductive polymer-coated tin-carbon negative electrode material is 200nm-5μm;

[0014] E. The ratio of the mass of the mixed conductive polymer coating layer to the sum of the mass of the elemental tin core and the amorphous carbon shell is (0.1-20): 100;

[0015] F. The ionic conductivity of the mixed conductive polymer coating is 10 -1 S / cm-10 -3 S / cm;

[0016] G. The electronic conductivity of the mixed conductive polymer coating is 10 -3 S / cm-10 2 S / cm.

[0017] The present application also provides a method for preparing a mixed conductive polymer-coated tin-carbon negative electrode material, comprising:

[0018] Mixing a carboxyl-rich organic tin source, a hydroxyl-rich carbon source and first water to perform a hydrothermal reaction to obtain a precursor;

[0019] Carbonizing the precursor in an inert atmosphere to obtain a carbonized material;

[0020] The carbonized material is mixed with a polymer solid electrolyte, an electronically conductive material, and a second water, dried, and subjected to microwave treatment to obtain the mixed conductive polymer-coated tin-carbon negative electrode material.

[0021] In some embodiments, at least one of the following conditions is met:

[0022] A. the carboxyl-rich organic tin source comprises one or a combination of tin oxalate, dimethyltin, dioctyltin, tetraphenyltin, tin methanesulfonate, and dibutyltin;

[0023] B. The hydroxyl-rich carbon source includes one or a combination of glucose, sucrose, maltose, lactose, fructose, starch, and cellulose;

[0024] C. The mass ratio of the carboxyl-rich organic tin source to the hydroxyl-rich carbon source is (1-20): 100;

[0025] D. the ratio of the sum of the mass of the carboxyl-rich organic tin source and the hydroxyl-rich carbon source to the mass of the first water is 1:(1-20);

[0026] E. The temperature of the hydrothermal reaction is 50-200°C and the time is 2-12 hours.

[0027] In some embodiments, at least one of the following conditions is met:

[0028] A. The inert atmosphere is an inert atmosphere or an oxygen-deficient atmosphere; the inert atmosphere includes any one or a combination of nitrogen atmosphere, argon atmosphere, neon atmosphere, helium atmosphere, xenon atmosphere or krypton atmosphere; the oxygen-deficient atmosphere is a gas atmosphere with an oxygen content of ≤1wt%;

[0029] B. The carbonization temperature is 400°C-800°C, and the holding time is 0.5-24h;

[0030] Optionally, the carbonization temperature is 500° C.-600° C., and the insulation time is 1-5 h.

[0031] In some embodiments, at least one of the following conditions is met:

[0032] A. The ratio of the sum of the mass of the polymer solid electrolyte and the electronic conductive material to the mass of the carbonized material is (0.1-20):100;

[0033] B. The carbonized material is mixed with the polymer solid electrolyte, the electronic conductive material and the second water at a stirring speed of 100-3000 rpm and a stirring time of 0.5-24 h;

[0034] C. The drying temperature is 50-200°C;

[0035] D. The microwave frequency of the microwave treatment is 100-3000 Hz, and the time of the microwave treatment is 10s-120s.

[0036] The present application also provides a negative electrode sheet, comprising the mixed conductive polymer-coated tin-carbon negative electrode material as described above, or comprising the mixed conductive polymer-coated tin-carbon negative electrode material prepared by the above preparation method.

[0037] The present application also provides a sodium ion battery, comprising the above-mentioned negative electrode sheet.

[0038] The present application also provides an electrical device, comprising the above-mentioned sodium ion battery.

[0039] Compared with the prior art, the beneficial effects of this application include:

[0040] The hybrid conductive polymer-coated tin-carbon negative electrode material provided in the present application has a single substance tin as the core, an amorphous carbon shell as the first coating layer, the carbon layer has a certain mechanical strength and toughness, which can limit the volume expansion of tin, and the second coating layer is a polymer solid electrolyte and an electronic conductive mixed layer, the polymer solid electrolyte has good elasticity, and can effectively inhibit volume expansion. On the basis of inhibiting volume expansion, the first coating layer and the second coating layer, the polymer solid electrolyte and the electronic conductive material improve the ionic conductivity and electronic conductivity, make the sodium ion embedding / extraction of tin more uniform, can further protect the interface of tin, improve the interface stability, and thus improve the cycle performance.

[0041] The preparation method of the mixed conductive polymer-coated tin-carbon negative electrode material provided in the present application uses a carboxyl-rich organic tin source and a hydroxyl-rich carbon source as raw materials for a hydrothermal reaction, wherein the carboxyl-rich organic tin source is first thermally decomposed into tin oxide and carboxyl functional groups, and the carboxyl functional groups are esterified and cross-linked with the hydroxyl-rich carbon source to form a spherical carbon precursor and a tin oxide precursor, and the tin oxide precursor is carbon-reduced at high temperature to generate a single tin core in situ, and the esterified cross-linked structure uniformly forms an amorphous carbon shell on the surface to obtain a spherical tin-carbon negative electrode material, which is then mixed with a polymer solid electrolyte and an electronic conductive material, dried, and subjected to microwave treatment, and the electronic conductive material receives the microwave magnetic field to generate heat, thereby enhancing the interaction between the mixed conductive polymer material and the amorphous carbon shell, and forming a uniform and firm mixed conductive polymer coating layer.

[0042] The negative electrode sheet, sodium ion battery and electrical equipment provided in the present application adopt the mixed conductive polymer-coated tin-carbon negative electrode material of the present application, which has high capacity and good cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0044] Figure 1 This is a schematic diagram of the structure of the mixed conductive polymer-coated tin-carbon negative electrode material of the present application;

[0045] Figure 2 This is a schematic diagram of the preparation process of the mixed conductive polymer-coated tin-carbon negative electrode material of the present application;

[0046] Figure 3 This is a SEM image of the mixed conductive polymer-coated tin-carbon negative electrode material of Example 1;

[0047] Figure 4 The charge and discharge curve test results of Examples 1 to 3 are shown;

[0048] Figure 5It is a long cycle test result diagram of Example 1 to Example 3;

[0049] Figure 6 The charge and discharge curve test results of Example 1 and Comparative Example 1 are shown;

[0050] Figure 7 It is a long cycle test result diagram of Example 1 and Comparative Example 1;

[0051] Figure 8 The charge and discharge curve test results of Example 1 and Comparative Example 2 are shown in FIG.

[0052] Fig. 9 It is a long cycle test result diagram of Example 1 and Comparative Example 2;

[0053] Fig.10 The charge and discharge curve test results of Example 1 and Comparative Example 3 are shown;

[0054] Fig.11 It is a long cycle test result diagram of Example 1 and Comparative Example 3;

[0055] Fig.12 The charge and discharge curve test results of Example 1 and Comparative Example 4 are shown;

[0056] Fig.13 It is a long cycle test result diagram of Example 1 and Comparative Example 4;

[0057] Fig.14 The charge and discharge curve test results of Example 1 and Comparative Example 5 are shown;

[0058] Fig.15 It is a graph showing the long cycle test results of Example 1 and Comparative Example 5. DETAILED DESCRIPTION

[0059] As used herein:

[0060] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0061] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0062] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0063] In these examples, parts and percentages are by mass unless otherwise indicated.

[0064] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.

[0065] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0066] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0067] This application provides a mixed conductive polymer coated tin-carbon negative electrode material, please refer to Figure 1, comprising: a single tin core, an amorphous carbon shell covering the single tin core, and a mixed conductive polymer coating layer covering the amorphous carbon shell, wherein the mixed conductive polymer coating layer has ionic conductivity and electronic conductivity.

[0068] The hybrid conductive polymer-coated tin-carbon negative electrode material provided in the present application has a single substance tin as the core, an amorphous carbon shell as the first coating layer, the carbon layer has a certain mechanical strength and toughness, which can limit the volume expansion of tin, and the second coating layer is a polymer solid electrolyte and an electronic conductive mixed layer, the polymer solid electrolyte has good elasticity, and can effectively inhibit volume expansion. On the basis of inhibiting volume expansion, the first coating layer and the second coating layer, the polymer solid electrolyte and the electronic conductive material improve the ionic conductivity and electronic conductivity, make the sodium ion embedding / extraction of tin more uniform, can further protect the interface of tin, improve the interface stability, and thus improve the cycle performance.

[0069] In some embodiments, the hybrid conductive polymer coating comprises a polymer solid electrolyte and an electronically conductive material.

[0070] In some embodiments, the electronically conductive material includes one or a combination of conductive carbon black, conductive graphite, single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, and carbon fibers.

[0071] In some embodiments, the polymer solid electrolyte includes one or a combination of polyethylene oxide, polyacrylonitrile, and poly(methyl methacrylate).

[0072] In some embodiments, the mass ratio of the polymer solid electrolyte to the electronic conductive material is 1:100 to 100:1, for example, it can be any ratio of 1:100, 1:90, 1:80, 1:70, 1:60, 1:50, 1:40, 1:30, 1:20, 1:10, 10:1, 20:1, 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, 90:1, 100:1 or a range between any two ratios, or any other ratio between 1:100 and 100:1 or any other range of values.

[0073] In some embodiments, the diameter of the elemental tin core is 100-2000nm, for example, it can be any value of 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1100nm, 1200nm, 1300nm, 1400nm, 1500nm, 1600nm, 1700nm, 1800nm, 1900nm, 2000nm or a range between any two values, or it can be any other value between 100-2000nm or any other range of values.

[0074] Optionally, the diameter of the elemental tin core is 800nm-2000nm.

[0075] In some embodiments, the thickness of the amorphous carbon shell is 10-200 nm, for example, it can be any value of 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm, or a range between any two values, or any other value between 10-200 nm or any other range of values.

[0076] Optionally, the amorphous carbon shell has a thickness of 20-100 nm.

[0077] In some embodiments, the thickness of the mixed conductive polymer coating is 10-200 nm, for example, it can be any value of 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm, or a range between any two values, or any other value between 10-200 nm or any other range of values.

[0078] Optionally, the thickness of the mixed conductive polymer coating layer is 20-100 nm.

[0079] In some embodiments, the particle size of the mixed conductive polymer-coated tin-carbon negative electrode material is 200nm-5μm, for example, it can be 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1100nm, 1200nm, 1300nm, 1400nm, 1500nm, 1600nm, 1700nm, 1800nm, 1900nm, 2000nm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, any value or a range between any two values, or any other value between 200nm-5μm or any other range of values.

[0080] Optionally, the particle size of the mixed conductive polymer-coated tin-carbon negative electrode material is 1 μm-5 μm.

[0081] In some embodiments, the ratio of the mass of the mixed conductive polymer coating to the sum of the masses of the elemental tin core and the amorphous carbon shell is (0.1-20):100, for example, it can be any ratio of 0.1:100, 1:100, 2:100, 3:100, 4:100, 5:100, 6:100, 7:100, 8:100, 9:100, 10:100, 11:100, 12:100, 13:100, 14:100, 15:100, 16:100, 17:100, 18:100, 19:100, 20:100 or a range between any two ratios, or it can be any other ratio between (0.1-20):100 or any other range of values.

[0082] In some embodiments, the ionic conductivity of the mixed conductive polymer coating is 10 -1 S / cm-10 -3 S / cm, for example, can be 10 -1 S / cm, 8×10 -2 S / cm, 5×10 -2 S / cm, 10 -2 S / cm, 5×10 -3 S / cm, 10 -3 Any value or range between any two values ​​in S / cm, or 10 -1 S / cm-10 -3 Any other value or any other range of values ​​between S / cm.

[0083] In some embodiments, the electronic conductivity of the mixed conductive polymer coating is 10 -3 S / cm-10 2 S / cm, for example, can be 10 -3 S / cm, 5×10-3 S / cm, 10 -2 S / cm, 5×10 -2 S / cm, 10 -1 S / cm, 5×10 -1 S / cm, 10 1 S / cm, 5×10 1 S / cm, 10 2 Any value or range between any two values ​​in S / cm, or 10 -3 S / cm-10 2 Any other value or any other range of values ​​between S / cm.

[0084] The present application also provides a method for preparing a mixed conductive polymer coated tin-carbon negative electrode material. Figure 2 ,include:

[0085] S100: mixing a carboxyl-rich organic tin source, a hydroxyl-rich carbon source and first water to perform a hydrothermal reaction to obtain a precursor;

[0086] S200: carbonizing the precursor in an inert atmosphere to obtain a carbonized material;

[0087] S300: mixing the carbonized material with a polymer solid electrolyte, an electronically conductive material, and a second water, drying, and subjecting to microwave treatment to obtain a mixed conductive polymer-coated tin-carbon negative electrode material.

[0088] The preparation method of the mixed conductive polymer-coated tin-carbon negative electrode material provided in the present application uses a carboxyl-rich organic tin source and a hydroxyl-rich carbon source as raw materials for a hydrothermal reaction, wherein the carboxyl-rich organic tin source is first thermally decomposed into tin oxide and carboxyl functional groups, and the carboxyl functional groups are esterified and cross-linked with the hydroxyl-rich carbon source to form a spherical carbon precursor and a tin oxide precursor, and the tin oxide precursor is carbon-reduced at high temperature to generate a single tin core in situ, and the esterified cross-linked structure uniformly forms an amorphous carbon shell on the surface to obtain a spherical tin-carbon negative electrode material, which is then mixed with a polymer solid electrolyte and an electronic conductive material, dried, and subjected to microwave treatment, and the electronic conductive material receives the microwave magnetic field to generate heat, thereby enhancing the interaction between the mixed conductive polymer material and the amorphous carbon shell, and forming a uniform and firm mixed conductive polymer coating layer.

[0089] In some embodiments, the carboxyl-rich organic tin source in step S100 includes one or a combination of tin oxalate, dimethyltin, dioctyltin, tetraphenyltin, tin methanesulfonate, and dibutyltin; the hydroxyl-rich carbon source includes one or a combination of glucose, sucrose, maltose, lactose, fructose, starch, and cellulose.

[0090] In some embodiments, the mass ratio of the carboxyl-rich organotin source to the hydroxyl-rich carbon source in step S100 is (1-20):100, for example, it can be any ratio of 1:100, 2:100, 3:100, 4:100, 5:100, 6:100, 7:100, 8:100, 9:100, 10:100, 11:100, 12:100, 13:100, 14:100, 15:100, 16:100, 17:100, 18:100, 19:100, 20:100 or a range between any two ratios, or it can be any other ratio between (1-20):100 or any other range of values.

[0091] In some embodiments, the ratio of the sum of the masses of the carboxyl-rich organic tin source and the hydroxyl-rich carbon source in step S100 to the mass of the first water is 1:(1-20), for example, it can be any ratio of 1:1, 1:5, 1:10, 1:15, 1:20 or a range between any two ratios, or any other ratio between 1:(1-20) or any other range of values.

[0092] In some embodiments, the temperature of the hydrothermal reaction in step S100 is 50-200°C, for example, it can be any value of 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, or any range between any two values, or any other value between 50-200°C or any other range of values, and the time is 2-12 hours, for example, it can be any value of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, or any range between any two values, or any other value between 2-12 hours or any other range of values.

[0093] In some embodiments, the inert atmosphere in step S200 is an inert atmosphere or an oxygen-deficient atmosphere; the inert atmosphere includes any one or a combination of nitrogen atmosphere, argon atmosphere, neon atmosphere, helium atmosphere, xenon atmosphere or krypton atmosphere; the oxygen-deficient atmosphere is a gas atmosphere with an oxygen content ≤1wt%.

[0094] In some embodiments, the carbonization temperature in step S200 is 400°C-800°C, for example, it can be any value of 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, or a range between any two values, or any other value between 400°C and 800°C, or any other range of values, and the insulation time is 0.5-24h, for example, it can be any value of 0.5h, 1h, 2h, 5h, 10h, 12h, 15h, 18h, 20h, 22h, 24h, or a range between any two values, or any other value between 0.5-24h or any other range of values.

[0095] Optionally, the carbonization temperature is 500° C.-600° C., and the insulation time is 1-5 h.

[0096] In some embodiments, the ratio of the sum of the masses of the polymer solid electrolyte and the electronic conductive material to the mass of the carbonized material in step S300 is (0.1-20):100, for example, it can be any ratio of 0.1:100, 1:100, 2:100, 3:100, 4:100, 5:100, 6:100, 7:100, 8:100, 9:100, 10:100, 11:100, 12:100, 13:100, 14:100, 15:100, 16:100, 17:100, 18:100, 19:100, 20:100 or a range between any two ratios, or it can be any other ratio between (0.1-20):100 or any other range of values.

[0097] In some embodiments, in step S300, the carbonized material is mixed with the polymer solid electrolyte, the electronic conductive material, and the second water at a stirring speed of 100-3000 rpm and a stirring time of 0.5-24 h.

[0098] In some embodiments, the drying temperature in step S300 is 50-200°C, for example, it can be any value of 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, or a range between any two values, or it can be any other value between 50-200°C or any other range of values.

[0099] In some embodiments, the microwave frequency of the microwave treatment in step S300 is 100-3000 Hz, for example, it can be any value of 100 Hz, 200 Hz, 300 Hz, 500 Hz, 800 Hz, 1000 Hz, 1200 Hz, 1500 Hz, 1700 Hz, 2000 Hz, 2300 Hz, 2500 Hz, 2800 Hz, 3000 Hz, or any other value between 100-3000 Hz, or any other range of values, and the time of the microwave treatment is 10s-120s, for example, it can be any value of 10s, 20s, 30s, 40s, 50s, 60s, 70s, 80s, 90s, 100s, 110s, 120s, or any other value between 10s-120s, or any other value in other range of values.

[0100] The present application also provides a negative electrode sheet, comprising the mixed conductive polymer-coated tin-carbon negative electrode material as described above, or comprising the mixed conductive polymer-coated tin-carbon negative electrode material prepared by the above preparation method.

[0101] The present application also provides a sodium ion battery, comprising the above-mentioned negative electrode sheet.

[0102] The present application also provides an electrical device, comprising the above-mentioned sodium ion battery.

[0103] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0104] Example 1

[0105] This embodiment provides a mixed conductive polymer coated tin-carbon negative electrode material, and the preparation method thereof comprises the following steps:

[0106] (1) Tin oxalate and glucose are mixed evenly in a mass ratio of 1:10, and pure water of equal mass to the powder is added, placed in a reaction kettle, heated to 120° C., kept warm for 8 hours, and cooled to room temperature to obtain a spherical precursor, wherein the precursor includes a carbon precursor and a tin oxide precursor.

[0107] (2) The precursor obtained in step (1) is taken out, ball-milled to a median particle size of about 5.0 μm, and added to a tubular furnace. The temperature is raised to 500° C. in a nitrogen atmosphere in the tubular furnace, kept warm for 3 h, and cooled to obtain a spherical carbonized tin-carbon negative electrode material.

[0108] (3) The carbonized material was then mixed with polymer solid electrolyte ethylene oxide and electronic conductive material single-walled carbon nanotubes in a mass ratio of 100:15:1, and pure water of equal mass to the powder was added, the speed was 2000r / min, stirred for 2h, centrifuged to remove the filtrate, and dried at 80°C. The dried material was then placed in a microwave treatment instrument, the microwave frequency was set to 2000Hz, and the microwave treatment time was 30s to obtain the mixed conductive polymer-coated tin-carbon negative electrode material of Example 1, and its SEM image is as follows Figure 3 shown.

[0109] Example 2

[0110] This embodiment provides a mixed conductive polymer coated tin-carbon negative electrode material, and the preparation method thereof comprises the following steps:

[0111] (1) Tin methanesulfonate and cellulose are mixed evenly at a mass ratio of 15:100, and pure water twice the mass of the powder is added, placed in a reaction kettle, heated to 150° C., kept warm for 5 hours, and cooled to room temperature to obtain a spherical precursor, wherein the precursor includes a carbon precursor and a tin oxide precursor.

[0112] (2) The precursor obtained in step (1) is taken out, ball-milled to a median particle size of about 7.0 μm, and added to a tubular furnace. The temperature is raised to 600° C. in a nitrogen atmosphere in the tubular furnace, kept warm for 2 h, and cooled to obtain a spherical carbonized tin-carbon negative electrode material.

[0113] (3) The carbonized material was then mixed with the polymer solid electrolyte polyacrylonitrile and the electronic conductive material carbon black in a mass ratio of 100:6:4, and pure water twice the mass of the powder was added, the speed was 1000 r / min, stirred for 4 hours, centrifuged to remove the filtrate, and dried at 100° C. The dried material was then placed in a microwave treatment instrument, the microwave frequency was set to 1000 Hz, and the microwave treatment time was 60 seconds to obtain the mixed conductive polymer-coated tin-carbon negative electrode material of Example 2.

[0114] Example 3

[0115] This embodiment provides a mixed conductive polymer coated tin-carbon negative electrode material, and the preparation method thereof comprises the following steps:

[0116] (1) Dimethyltin and starch are mixed uniformly in a mass ratio of 1:5, and pure water 10 times the mass of the powder is added, placed in a reaction kettle, heated to 80° C., kept warm for 12 hours, and cooled to room temperature to obtain a spherical precursor, wherein the precursor includes a carbon precursor and a tin oxide precursor.

[0117] (2) The precursor obtained in step (1) is taken out, ball-milled to a median particle size of about 3.0 μm, and added to a tubular furnace. The temperature is raised to 500° C. in a nitrogen atmosphere in the tubular furnace, kept warm for 24 h, and cooled to obtain a spherical carbonized tin-carbon negative electrode material.

[0118] (3) The carbonized material was then mixed with the polymer solid electrolyte polymethyl methacrylate and the electronic conductive material multi-walled carbon nanotubes in a mass ratio of 100:18:2, and pure water 1.5 times the mass of the powder was added, the speed was 3000 r / min, stirred for 1.5 hours, centrifuged to remove the filtrate, and dried at 60° C. The dried material was then placed in a microwave treatment instrument, the microwave frequency was set to 3000 Hz, and the microwave treatment time was 10 seconds to obtain the mixed conductive polymer-coated tin-carbon negative electrode material of Example 3.

[0119] Comparative Example 1

[0120] This comparative example provides a mixed conductive polymer coated tin-carbon negative electrode material, and the preparation method thereof comprises the following steps:

[0121] (1) Glucose and sodium hydroxide were mixed in a mass ratio of 1:1 and placed in a tube furnace. The temperature was raised to 500°C under a nitrogen atmosphere, kept at this temperature for 3 hours, and cooled to obtain porous hard carbon. The mass ratio of porous hard carbon to molten metal tin was 10:1, and the mixture was evenly mixed by ball milling to obtain tin-doped hard carbon material.

[0122] (2) The tin-doped hard carbon material obtained in step (1) is mixed with polymer solid electrolyte ethylene oxide and electronic conductive material single-walled carbon nanotubes in a mass ratio of 100:15:1, pure water of equal mass to the powder is added, the speed is 2000r / min, stirred for 2h, centrifuged to remove the filtrate, and dried at 80°C. Subsequently, the dried material is placed in a microwave treatment instrument, the microwave frequency is set to 2000Hz, and the microwave treatment time is 30s, to obtain the mixed conductive polymer-coated tin-carbon negative electrode material with the core of the tin-doped porous carbon material of Comparative Example 1.

[0123] Comparative Example 2

[0124] Comparative Example 2 provides a carbon-coated composite tin-carbon negative electrode material, and its preparation method is different from that of Example 1 in that: step (3) is not performed in Comparative Example 2, and the material obtained in step (2) is not added with polymer solid electrolyte and electronic conductive material for microwave treatment to obtain a spherical single-layer carbon-coated composite tin-carbon negative electrode material.

[0125] Comparative Example 3

[0126] Comparative Example 3 provides a double-layer carbon-coated composite tin-carbon negative electrode material, and its preparation method is different from that of Example 1 in that: the microwave frequency in step (3) is set to 4000 Hz, the microwave treatment time is 600 s, and the coating layer is completely carbonized by microwaves to obtain a double-layer carbon-coated composite tin-carbon negative electrode material.

[0127] Comparative Example 4

[0128] Comparative Example 4 provides a polymer solid electrolyte coated tin-carbon negative electrode material, and its preparation method is different from that of Example 1 in that: in Comparative Example 4, no electronic conductive material is added in step (3) for microwave treatment to obtain a polymer electrolyte coated composite tin-carbon negative electrode material.

[0129] Comparative Example 5

[0130] Comparative Example 5 provides an electronically conductive coated tin-carbon negative electrode material, and its preparation method differs from that of Example 1 in that: in Comparative Example 5, no polymer solid electrolyte material is added for microwave treatment in step (3) to obtain an electronically conductive coated composite tin-carbon negative electrode material.

[0131] The electrochemical performance of the tin-carbon negative electrode materials obtained in each embodiment and comparative example was tested respectively. The specific button battery electrode sheet was prepared by a method known in the art: the negative electrode material, the conductive agent and the binder were adjusted to a solid content of 50% with deionized water in a mass percentage of 91:3:6, and mixed evenly, coated on a copper foil current collector, vacuum dried, and rolled to a surface density of 5.5±0.5 mg / cm 2 , and the negative electrode sheet is obtained.

[0132] Button cell production: sodium sheet is used as the counter electrode, 1 mol / L NaPF6 / DIGLYME (100 Vol%) is used as the electrolyte, glass fiber is used as the diaphragm, and a 2032 button cell shell is used to assemble the button half cell.

[0133] The electrochemical test results of Examples 1 to 3 are as follows: Figure 4 and Figure 5 As shown, the electrochemical test results of Example 1 and Comparative Example 1 are as follows Figure 6 and Figure 7 As shown, the electrochemical test results of Example 1 and Comparative Example 2 are as follows Figure 8 and Fig. 9 As shown, the electrochemical test results of Example 1 and Comparative Example 3 are as follows Fig.10 and Fig.11 As shown, the electrochemical test results of Example 1 and Comparative Example 4 are as follows Fig.12 and Fig.13 As shown, the electrochemical test results of Example 1 and Comparative Example 5 are as follows Fig.14 and Fig.15 shown.

[0134] The electrochemical properties of the tin-carbon negative electrode materials of various embodiments and comparative examples are shown in Table 1.

[0135] Table 1 Electrochemical properties of tin-carbon negative electrode materials of various embodiments and comparative examples

[0136]

[0137] According to Table 1, the number of cycles of the tin-carbon negative electrode materials of Examples 1 to 3 of the present application with a cycle capacity retention rate of 90% can all reach more than 1,000 times, while the number of cycles of the comparative solution with a cycle capacity retention rate of 90% can only reach 571 times at most. Among them, although the charge-discharge capacity and the first effect of the mixed conductive polymer-coated tin-carbon negative electrode material whose core is a tin-doped porous carbon material in Comparative Example 1 are higher than those of the embodiment scheme, its number of cycles is only 94 times. In Comparative Example 1, the metallic tin exists in the porous carbon and is not completely coated as in Example 1. Part of the metallic tin is exposed. Although the reaction area between the metallic tin and the electrolyte is increased to a certain extent, making the first effect and the charge-discharge capacity higher, the interface of the exposed part of the metallic tin deteriorates after multiple cycles, causing the material to expand, rupture and pulverize, resulting in a significant decrease in the cycle performance.

[0138] The single-layer carbon-coated composite tin carbon negative electrode material of Comparative Example 2, the double-layer carbon-coated composite tin carbon negative electrode material of Comparative Example 3, the polymer electrolyte-coated composite tin carbon negative electrode material of Comparative Example 4, and the electronic conductivity-coated composite tin carbon negative electrode material of Comparative Example 5 are all inferior to the embodiment scheme in terms of charge and discharge capacity, first effect, or the number of cycles with a cycle capacity retention rate of 90%. This is because Comparative Examples 2 and 3 do not have a mixed conductive polymer coating layer composed of a polymer solid electrolyte and an electronic conductive material, and the ionic conductivity and electronic conductivity are poor, and the sodium ion embedding / extraction of tin is uneven, and the stability of the tin interface cannot be protected, thereby affecting the cycle performance. The second coating layer of Comparative Example 4 has only ionic conductivity and poor electronic conductivity, which can easily increase the polarization of the battery in multiple cycles, affecting the cycle performance; the second coating layer of Comparative Example 5 has only electronic conductivity and poor ionic conductivity, and the sodium ion embedding / extraction of metal tin is uneven and slow, which can easily cause local enrichment and deposition of sodium ions, affecting the cycle performance.

[0139] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

[0140] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. A mixed conductive polymer coated tin-carbon negative electrode material, characterized in that: include: A single tin core, an amorphous carbon shell covering the single tin core, and a mixed conductive polymer coating layer covering the amorphous carbon shell, wherein the mixed conductive polymer coating layer has ionic conductivity and electronic conductivity.

2. The hybrid conductive polymer-coated tin-carbon negative electrode material according to claim 1, characterized in that: The mixed conductive polymer coating layer includes a polymer solid electrolyte and an electronic conductive material; Optionally, the electronic conductive material includes one or a combination of conductive carbon black, conductive graphite, single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, and carbon fibers; Optionally, the polymer solid electrolyte includes one or a combination of polyethylene oxide, polyacrylonitrile, and poly(methyl methacrylate); Optionally, the mass ratio of the polymer solid electrolyte to the electronic conductive material is 1:100 to 100:

1.

3. The mixed conductive polymer-coated tin-carbon negative electrode material according to claim 1 or 2, characterized in that: At least one of the following conditions is met: A. The diameter of the elemental tin core is 100-2000nm; B. The thickness of the amorphous carbon shell is 10-200 nm; C. The thickness of the mixed conductive polymer coating layer is 10-200 nm; D. The particle size of the mixed conductive polymer-coated tin-carbon negative electrode material is 200nm-5μm; E. The ratio of the mass of the mixed conductive polymer coating layer to the sum of the mass of the elemental tin core and the amorphous carbon shell is (0.1-20): 100; F. The ionic conductivity of the mixed conductive polymer coating is 10 -1 S / cm-10 -3 S / cm; G. The electronic conductivity of the mixed conductive polymer coating is 10 -3 S / cm-10 2 S / cm.

4. A method for preparing a mixed conductive polymer-coated tin-carbon negative electrode material, characterized in that: include: Mixing a carboxyl-rich organic tin source, a hydroxyl-rich carbon source and first water to perform a hydrothermal reaction to obtain a precursor; Carbonizing the precursor in an inert atmosphere to obtain a carbonized material; The carbonized material is mixed with a polymer solid electrolyte, an electronically conductive material, and a second water, dried, and subjected to microwave treatment to obtain the mixed conductive polymer-coated tin-carbon negative electrode material.

5. The method for preparing the mixed conductive polymer-coated tin-carbon negative electrode material according to claim 4, characterized in that: At least one of the following conditions is met: A. the carboxyl-rich organic tin source comprises one or a combination of tin oxalate, dimethyltin, dioctyltin, tetraphenyltin, tin methanesulfonate, and dibutyltin; B. The hydroxyl-rich carbon source includes one or a combination of glucose, sucrose, maltose, lactose, fructose, starch, and cellulose; C. The mass ratio of the carboxyl-rich organic tin source to the hydroxyl-rich carbon source is (1-20): 100; D. the ratio of the sum of the mass of the carboxyl-rich organic tin source and the hydroxyl-rich carbon source to the mass of the first water is 1:(1-20); E. The temperature of the hydrothermal reaction is 50-200°C and the time is 2-12 hours.

6. The method for preparing the mixed conductive polymer-coated tin-carbon negative electrode material according to claim 4, characterized in that: At least one of the following conditions is met: A. The inert atmosphere is an inert atmosphere or an oxygen-deficient atmosphere; the inert atmosphere includes any one or a combination of nitrogen atmosphere, argon atmosphere, neon atmosphere, helium atmosphere, xenon atmosphere or krypton atmosphere; the oxygen-deficient atmosphere is a gas atmosphere with an oxygen content of ≤1wt%; B. The carbonization temperature is 400°C-800°C, and the holding time is 0.5-24h; Optionally, the carbonization temperature is 500° C.-600° C., and the insulation time is 1-5 h.

7. The method for preparing the mixed conductive polymer-coated tin-carbon negative electrode material according to claim 4, characterized in that: At least one of the following conditions is met: A. The ratio of the sum of the mass of the polymer solid electrolyte and the electronic conductive material to the mass of the carbonized material is (0.1-20):100; B. The carbonized material is mixed with the polymer solid electrolyte, the electronic conductive material and the second water at a stirring speed of 100-3000 rpm and a stirring time of 0.5-24 h; C. The drying temperature is 50-200°C; D. The microwave frequency of the microwave treatment is 100-3000 Hz, and the time of the microwave treatment is 10s-120s.

8. A negative electrode sheet, characterized in that: The invention comprises the mixed conductive polymer coated tin-carbon negative electrode material as described in any one of claims 1 to 3, or comprises the mixed conductive polymer coated tin-carbon negative electrode material prepared by the preparation method as described in any one of claims 4 to 7.

9. A sodium ion battery, characterized in that: Includes the negative electrode sheet as described in claim 8.

10. An electrical equipment, characterized in that: Including the sodium ion battery as described in claim 9.

Citation Information

Patent Citations

  • Preparation method of carbon-coated elemental tin material, and application of tin material in lithium ion battery

    CN107658443A

  • Fast charge composite graphite material and preparation method thereof

    CN113764644A

  • Tin-carbon composite material and preparation method and application thereof

    CN114400307A

  • Tin-based alloy hard carbon composite material and preparation method thereof

    CN117276518A

  • Negative active material, negative plate, preparation method and battery

    CN118919678A

Cited By

  • Preparation method of tin-antimony-sodium alloy / carbon composite negative electrode material based on Na15Sn4 precursor

    CN121439767A